The practical and theoretical feeding of laying hens. - Van Dorp, Fred (My University, 1905)
Introduction: The subject of stock-feeding as related to poultry, is hardly appreciated by most farmers and poultry breeders of this State. Poultry keeping as a special business or an extended branch of other farming is not carried on as yet to any extent. In the Eastern part of the United States, especially, this is an important occupation, and all of the State Experiment Stations are doing considerable work along this line. To the general farmer of this State, a little knowledge of how to feed his flock of hens would increase his winter income as does the improved methods of feeding his other livestock. But to the one who keeps laying hens on an extended scale for the most profit, this subject is of the greatest importance. Is he feeding more than is necessary for the maintenance and the maximum egg production? Is he feeding protein in one find of feed when he can feed it in a different form for one fourth less money? Is he feeding nutrients in the proper proportions? These are questions to be studied. The present haphazard methods require it. Each has his own method, which his own narrow experience has taught him is the most successful. No two poultry –men feed alike, and on a great many feeding questions they have many diverse opinions of what is correct. The common method is to throw them what grain they will eat, usually corn, and let them do the rest. Balanced rations are as necessary for poultry, as for other stock. They do not always work out to be the best in practice, with the stock on the farm, but in the majority of cases they prove to be the most economical. All of the most successful dairy -men feed their cows reasonably well balanced rations. A balanced ration is necessary for the most economical consumption of food with poultry for the same reasons as other stock.
Citation: Van Dorp, Fred. The practical and theoretical feeding of laying hens.. Senior thesis, Kansas State Agricultural College, 1905.
Morse Department of Special Collections
Keywords: Necessity of Balanced Rations; Nutritive Ratio; Ground Grain Compared with Whole Grain; Theses